THE APPLICATION OF ASBUTON AND POLYMER MODIFIED BITUMEN FOR PAVEMENT MIXTURE DESIGN AT HOT AND ARID REGION - I. D. Matar, Mohammed; Setyawan, Agus; Sambowo, Kusno Adi (Jurnal Teknik Sipil, 2014)
AbstractMany of the studies have been done in finding other alternative material in order to using as polymer modified bitumen in asphalt mixes and Rock Asphalt on improvement its properties, highway quality And increase the ability to withstand changes in temperature in hot and arid regions Current rapid increases in traffic volume and legal weight increased loads on the road structure Different temperatures will make the asphalt less resilient to stresses inflicted It could reduce the service life and increase the cost of maintenance of the road. The mechanical properties of the asphalt paving mixtures were characterized at three testing permanent deformation, fatigue and cracking that is forcing engineers to consider these issue attempts to improve the quality and characteristics of asphalt pavement using additives. Many of the studies have been done in finding other alternative material in order to using as polymer modified bitumen in asphalt mixes and Rock Asphalt on improvement its properties, highway quality And increase the ability to withstand changes in temperature in hot and arid regions.In this study, the laboratory works can be divided into three stages: The First Stage, make tests in the laboratory on the following Aggregate materials, to know the physical properties and the possibilityknow their physical properties and specifications. The Third Stage, a total of 108 samples prepared from Asphalt (60/70 pen), ASBUTON and Polymer Modified Bitumen (Starbit E-55) all of them separately. Including Marshall Stability T of their use in the mixture. The Second Stage, make tests in the laboratory on the following bituminous materials: Asphalt 60/70 pen, ASBUTON and Polymer Modified Bitumen (Starbit E-55) all of them separately, to est (MS) to get OBC, (UCS), (ITS) with at (30ºC, 40ºC, 60ºC) and Permeability Test. The objective of that is a comparing the results of laboratory tests to know the best stable and resilient material at different temperatures. In comparison with the results of Marshall Test, it is noticed that Starbit E-55 mixture was more stable than Asphalt 60/70 pen and ASBUTON mixtures; the density of the Asphalt 60/70 pen mixture was higher than the density of the Starbit E-55 and ASBUTON mixtures respectively. The results of Permeability test shows that the Asphalt 60/70 pen mixture was less permeable than Starbit E-55 and ASBUTON mixtures respectively. The result of ITS and UCS test shows that Asphalt 60/70 pen mixture was higher performance than Starbit E-55 and ASBUTON mixtures at (30°C). Asphalt 60/70 pen mixture was less sensitive to temperature changes compare with Starbit E-55 and ASBUTON mixtures.Keywords: AC , Asphalt 60/70 pen, ASBUTON, PMB ( Starbit E-55), ITS test & UCS test @ (30 ºC , 40 ºC , 60 ºC), permeability test.